2020
DOI: 10.1002/adhm.202001268
|View full text |Cite
|
Sign up to set email alerts
|

Glial Interfaces: Advanced Materials and Devices to Uncover the Role of Astroglial Cells in Brain Function and Dysfunction

Abstract: Research over the past four decades has highlighted the importance of certain brain cells, called glial cells, and has moved the neurocentric vision of structure, function, and pathology of the nervous system toward a more holistic perspective. In this view, the demand for technologies that are able to target and both selectively monitor and control glial cells is emerging as a challenge across neuroscience, engineering, chemistry, and material science. Frequently neglected or marginally considered as a barrie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
31
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(31 citation statements)
references
References 216 publications
(373 reference statements)
0
31
0
Order By: Relevance
“…Engineering in vitro tissue models, for example, using hPSC-derived neural organoids (hNOs), is necessary to realize the effect of small molecules, drugs, and vaccines on the neuropathogenesis of COVID-19 [154]. Also, glial interfaces might enlighten us on precisely how COVID-19 behaves in the brain for the purpose of predicting its behavior in reality [155,156].…”
Section: Biomaterials For Modeling Covid-19-associated Brain Damagementioning
confidence: 99%
“…Engineering in vitro tissue models, for example, using hPSC-derived neural organoids (hNOs), is necessary to realize the effect of small molecules, drugs, and vaccines on the neuropathogenesis of COVID-19 [154]. Also, glial interfaces might enlighten us on precisely how COVID-19 behaves in the brain for the purpose of predicting its behavior in reality [155,156].…”
Section: Biomaterials For Modeling Covid-19-associated Brain Damagementioning
confidence: 99%
“…Astrocyte adhesion, growth and morphology can be altered or even driven by interactions with nanomaterials. 18,20,26,27,35,36 With respect to electrospun nanobres, previous data indicated that the topography is the major supercial clue driving adhesion and growth of astrocytes. 25 Accordingly, in the present work, the aligned nanobres display the best performance in terms of viability and growth of primary astrocytes over time.…”
Section: Effects Of Pani Electrospun Nanobre On the Viability And Momentioning
confidence: 99%
“…It has been widely demonstrated that changes in the functional properties of primary astrocytes can occur when these cells are grown on a nanostructured surface or on biocomposites with different compositions. 18,20,26,35,37 Recent and growing literature also describes that every cell type, including stem cells and glial cells, can sense the extracellular environment and change their electrical properties accordingly. 38 However, changes in the electrical properties of astrocytes can be observed during gliotic reactions occurring in response to biomaterial implants.…”
Section: Effects Of Pani Electrospun Nanobre On the Viability And Momentioning
confidence: 99%
See 2 more Smart Citations